Formation, segmentation and deep crustal structure variations along the Algerian margin from the SPIRAL seismic experiment. (February 2022) - Klingelhoefer, Frauke; Déverchère, Jacques; Graindorge, David; Aïdi, Chafik; Badji, Rabie; Bouyahiaoui, Boualem; Leprêtre, Angélique; Mihoubi, Abdelhafid; Beslier, Marie-Odile; Charvis, Philippe; Schnurle, Philippe; Sage, Francoise; et al.
Abstract: The Algerian continental margin in the western Mediterranean formed as a back-arc basin and is today reactivated by the convergence between the African and Eurasian plates. It is one of the very rare examples of passive margins undergoing inversion expressed in a moderate seismicity of the margin and is possibly giving way for future subduction. With the objective to better know the deep structure of the margin and its associated basin, the origin of its seismicity and to study the mechanism of reactivation, five existing wide-angle seismic profiles along the margin are revisited. They were located offshore Mostaganem, Tipasa, Greater Kabylia, Jijel and Annaba. These profiles show that the basin is underlain by a 5 km thick crust of oceanic magmatic origin, possibly created at non-continuous small accretionary ridge segments. The continent-ocean transition zone is narrow, except at the easternmost profile, possibly due to an opening including a shear movement. No high velocity zone in the lower crust corresponding to mantle rocks has been imaged at the Algerian margin. The continental crust is thinned in a narrow and strongly segmented manner. It is widest (70 km) in the central segment offshore Greater Kabylia where there is a wider zone of distal thinned continental crust than on the other margin segments. The thickest crust detected during this survey corresponds to the African continental crust and the Kabylides blocks and is about 22–25 km thick. This reduced thickness in comparison with unthinned continental crust might be due to the influence of earlier subduction at the margin, in form of erosion by the subducting slab. Highlights: Five regional seismic transects image the deep structure of the Algerian margin. A very narrow or absent COT is observed along all profiles. No high velocity zone in the lower oceanic crust has been imaged. The north Algerian Basin is underlain by a ∼5 km thin oceanic crust. The northwestern margin is influenced by a STEP fault.